Buginese Tradition “Massolo” in Soreang District, Parepare (Study of Islamic Law) - Sunuwati; Sulaeha; Fatjri Nur Tajuddin (Jurnal Marital: Kajian Hukum Keluarga Islam, 2022)
This research was conducted by taking the issue of how the implementation of the massolo’' tradition, the public's perception of the implementation of the massolo’' tradition, and how the views of Islamic law regarding to the implementation of the massolo’' tradition in the marriage of the Bugis community in Soreang District, Parepare City. The type of research used in this reserach is qualitative descriptive method, the data in this study were obtained from primary data and secondary data. The data collection technique used is observation, interview, and documentation, while the technique used in determining the sources is purposive sampling technique. The data analysis technique is using the triangulation technique. The results of this study indicate that: 1) The implementation of the massolo’ tradition in Bugis traditional marriages is to provide assistance in the form of money or goods to the invitees. The invitees are family or close relatives, friends or friends, and neighbors. Invitees invite through invitation cards, telephone, and messages either in the form of letters or through social media. The massolo’ activities were held at the house holding the event, the building, and the hotel. 2) Massolo’ is a tradition that occurs in society as a form of providing assistance and as a form of remuneration. The assistance provided can be in the form of goods, money and labor. Gifts from Massolo’ can be categorized as gifts, alms, or debts, but they are not bribes. 3) Massolo’ in the view of Islamic law is a form of mutual assistance. Massolo’ must be attended by everyone who is invited if there are no obstacles because massolo’ activities can strengthen ties of friendship with family, relatives, neighbors and friends.